Optimization of Zakat, Infaq and Shadaqah Punishment Through The Three Circles Model In Realizing Mustahik Welfare - Tiara, Mutiara Muslimah; Lemiyana; Chici Rima Putri Pratama (Jurnal I-Philanthropy, 2024)
Abstract: Realizing well-being is a state where individuals or groups of society seek to meet their material, spiritual, and social needs due to unmet requirements. This study aims to evaluate and optimize the distribution of Zakat, Infaq, and Shadaqah (ZIS) funds through the implementation of the Three Circles Model to achieve the well-being of mustahik at BAZNAS Kota Palembang. The Three Circles Model, developed by the Ministry of Religious Affairs of the Republic of Indonesia, integrates a holistic approach in ZIS fund management with a focus on three main areas: muzakki, amil, and mustahik, encompassing social, economic, and religious aspects. This research employs a mixed-methods approach, combining quantitative analysis of ZIS fund collection and distribution data with qualitative interviews with mustahik and amil at BAZNAS Kota Palembang. The findings indicate that during the first six months of 2024, BAZNAS Kota Palembang successfully collected a total of Rp3,968,830,416 in ZIS funds and allocated Rp2,645,040,148 to various programs, including "Palembang Peduli," "Palembang Sehat," "Palembang Makmur," "Palembang Cerdas," and "Palembang Taqwa." These programs have had a positive impact on improving the well-being of mustahik by meeting basic needs, improving housing conditions, providing health services, supporting education, and creating job opportunities. However, challenges such as fluctuations in fund collection and suboptimal allocation from the total funds collected were noted. This study recommends enhancing transparency and accountability in fund management, improving distribution mechanisms to reduce disparities, and developing more effective monitoring and evaluation systems. Additionally, suggestions for future research include studying long-term impacts, innovations in management, and comparative analysis with other zakat institutions. By implementing the Three Circles Model, BAZNAS Kota Palembang is expected to more effectively optimize the distribution of ZIS funds and achieve the goal of mustahik well-being in a more comprehensive and sustainable manner.